Medium-term Business Cycles in Developing Countries - Comin, Diego; Loayza, Norman; Pasha, Farooq; Serven, Luis (2012)
Empirical evidence - including the current global crisis - suggests that shocks from advanced countries often have a disproportionate effect on developing economies. Can this account for the fact that aggregate fluctuations are larger and more persistent in the latter than in the former economies? And what are the mechanisms at play? This paper addresses these questions using a model of an industrial and a developing economy trading goods and assets, with (i) a product cycle shaping the range of intermediate goods used to produce new capital in each country, and (ii) investment adjustment costs in the developing economy. Innovation by the advanced economy results in new intermediate goods, at first produced at home, and eventually transferred to the developing economy through direct investment. The pace of innovation and technology transfer is driven by profitability. This process of technology diffusion creates a medium-term connection between both economies, over and above the short-term link through trade. Calibration of the model to match Mexico-United States trade and foreign direct investment flows shows that this mechanism can explain why shocks to the United States economy have a larger effect on Mexico than on the United States itself, and hence why Mexico shows higher volatility than the United States; why business cycles in the United States lead to medium-term fluctuations in Mexico; and why consumption is not less volatile than output in Mexico.